Factor analysis for genetic evaluation of linear type traits in dual-purpose autochthonous breeds. (11th September 2015) - Mazza, S.; Guzzo, N.; Sartori, C.; Mantovani, R.
Abstract : Factor analysis was applied to individual type traits (TT) scored in primiparous cows belonging to two dual purpose Italian breeds, Rendena (REN; 20 individual type traits evaluated on 11 399 first parity cows), and Aosta Red Pied (ARP; 22 individual type traits evaluated on 36 168 primiparous cows). Six common latent factors (F1 to F6; eigenvalues ⩾1) which explained 63% (REN) and 58% (ARP) of the total variance were obtained. F1 included TT mainly related to muscularity, and F2 to body size. The F3 and F4 accounted for udder size and conformation, respectively. F5 included rear legs and feet. Biological significance for F6 was not readily obtained. Moderate to low heritability were estimated through REML single-trait analysis from factor scores (from 0.22 to 0.52 in REN, and from 0.08 to 0.37 in ARP). The greatest heritability values were estimated for body size and muscularity (0.52 and 0.37 for body size; and 0.40 and 0.32 for muscularity in REN and ARP, respectively). As expected, rank correlations, obtained considering estimated breeding values derived from best linear unbiased prediction analysis on the individual TT and factor score, showed similar coefficients to those observed in the factor analysis following loading of TT within each latent factor. These results suggest the possibility to implement the factor analysis in the morphological evaluation, simplifying the information given by the type traits into new variables useful for the genetic improvement of dual purpose cattle.